Correlation of Serum Amylase and Lipase Levels with Clinical Severity in Acute Pancreatitis - Anjum, Muhammad Burhan; Iqra; Arshad, Sohail; Haider, Romail; Khurram, Muhammad Aizad; Fatima, Adeeba (Indus Journal of Bioscience Research, 2025)
Background: Acute pancreatitis is an inflammatory condition of the pancreas with variable clinical presentations, ranging from mild, self-limiting symptoms to severe disease with multi-organ failure. Objective: To evaluate the correlation between serum amylase and lipase levels and the clinical severity of acute pancreatitis as defined by the Modified Atlanta Classification. Methods: This cross-sectional, observational study was conducted at Shalamar Hospital from October 2024 to March 2025. A total of 185 patients diagnosed with acute pancreatitis were enrolled in the study. Patients were selected through non-probability consecutive sampling technique. Upon admission, detailed demographic data including age, gender, and relevant history were recorded. Blood samples were obtained within 24 hours of presentation to measure serum amylase and lipase levels using standardized enzymatic colorimetric assays. Results: Out of 185 patients, 44.3% had mild, 34.6% had moderately severe, and 21.1% had severe acute pancreatitis. Mean serum amylase levels increased across severity groups (612 ± 180 U/L in mild, 685 ± 200 U/L in moderately severe, and 700 ± 220 U/L in severe; p = 0.09), but the trend was not statistically significant. Serum lipase levels showed a significant rise (980 ± 250 U/L, 1120 ± 310 U/L, and 1210 ± 340 U/L respectively; p = 0.01). A weak positive correlation was found between amylase and severity (Spearman’s rho = 0.21, p = 0.07), while lipase showed a moderate correlation (Spearman’s rho = 0.42, p < 0.001). ICU admission and mortality were observed exclusively in the severe group. Conclusion: Serum lipase levels demonstrate a moderate and statistically significant correlation with the clinical severity of acute pancreatitis and may serve as a valuable early predictor in triage settings. Serum amylase levels are less predictive of severity.